2007
DOI: 10.1097/ajp.0b013e318154b6c3
|View full text |Cite
|
Sign up to set email alerts
|

Unipedicular Vertebroplasty for Osteoporotic Compression Fracture Using an Individualized Needle Insertion Angle

Abstract: Unipedicular PVP can be performed safely, provided the operator has a thorough knowledge of the bony landmarks and the anatomy of the pedicle. A unipedicular approach could be considered first using individualized NIA at each vertebral level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…Additionally, the authors found that the unaugmented side of a laterally placed injection was not at an increased risk for collapse, as previously thought. 3,16,17 Our study has several limitations. The study was conducted retrospectively; thus, it was subject to bias.…”
Section: Discussionmentioning
confidence: 92%
“…Additionally, the authors found that the unaugmented side of a laterally placed injection was not at an increased risk for collapse, as previously thought. 3,16,17 Our study has several limitations. The study was conducted retrospectively; thus, it was subject to bias.…”
Section: Discussionmentioning
confidence: 92%
“…Also interpretation of fluoroscopic images is easier, since the introduction of the second cannula may obscure the field of vision. The majority of the studies in the literature, either biomechanical [7,9,17] or clinical [4,5,6,8,10], support its use and equivalent effectiveness with regard to the bilateral approach, with satisfactory cement filling and coronal alignment. However, few comparative studies have been published up to date; there are 4 studies on osteoporotic fractures [11,12,13,14,21] and 1 on cancer-related fractures [22].…”
Section: Discussionmentioning
confidence: 99%
“…Whereas the technique is intriguing, we find it complex and difficult to apply in comparison with our method. Another interesting technical note was published by Chang et al [6] in relation to the use of oblique fluoroscopy. The authors challenged the traditional 20° to 30° inclination of the C-arm suggested by others [5] and calculated the individual needle angle from an axial MRI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations